Using Gamification To Increase E-Learning Engagement - Sri Watini; Widhy Setyowati (International Transactions on Education Technology (ITEE), 2023)
E-learning is limited from a pedagogical standpoint because it can't emote or captivate students the same way a teacher can. To compensate for the lack of sensation or emotional engagement, an e-learning system must aim to encourage students in other ways. JB Fogg conducted study on the subject of persuasive technology and how to develop tools that affect a user's emotions. He introduces the Fogg's Behavior model, which looks into the circumstances that can lead to a particular behavior. There are numerous uses for this idea in human-computer interaction. Games are a regular aspect of life that delight players while also modeling behavior. We can improve user engagement with an e-learning application and its particular activities by incorporating game mechanics and dynamics into tasks and e-learning processes. Gamification is a term that has many applications in business practices and suggests tried-and-true methods that are comparable to those used in games. Gamification is the process of integrating elements of gaming into non-gaming applications, particularly user-friendly internet and mobile platforms. Furthermore, it seeks to persuade users to engage in the appropriate behaviors in respect to the applications. This description is connected to the terms serious games, serious gaming, playful engagement, and game-based technology. In this section, we'll examine each one in more detail, as well as examine how well they apply to e-learning and the learning process as a whole.